2010
DOI: 10.3892/or_00001046
|View full text |Cite
|
Sign up to set email alerts
|

Color flow mapping: a non-invasive tool for characterizing and differentiating between uveal melanomas and choroidal metastases

Abstract: Abstract. The objective of this study was to characterize and differentiate vascular patterns of choroidal melanomas and choroidal metastases by color flow mapping (CFM). We conducted a retrospective chart study on CFM findings in 18 patients with choroidal melanomas and 10 patients with choroidal metastases. We evaluated the possibilities of applying CFM to identify hypo-versus hyper-vascularity within the tumor, a central 'dominant vessel', and Doppler signals in the tumor's center and/or periphery. CFM demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The diagnosis of a choroidal tumor is based mainly on clinical characteristics. Additional diagnostic testing includes ultrasonography (US), fluorescein angiography, and color Doppler testing [ 1 ]. US enables localization of the intraocular mass, estimation of its size, and characterization of its tissue texture.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of a choroidal tumor is based mainly on clinical characteristics. Additional diagnostic testing includes ultrasonography (US), fluorescein angiography, and color Doppler testing [ 1 ]. US enables localization of the intraocular mass, estimation of its size, and characterization of its tissue texture.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we are aware, only one case of PDT for choroidal metastasis from carcinoid tumor has been reported previously 5. Choroidal metastasis has a hypervascular pattern, as demonstrated by color-flow mapping 20. Therefore, PDT may be effective for choroidal hemangioma and hypervascular choroidal tumors 21,22.…”
Section: Discussionmentioning
confidence: 98%
“…Color Doppler flow imaging allows real-time observation on the characteristics of blood flow in the tumor [8]. Previous literature has reported that choroidal metastases and choroidal melanomas can be differentiated based on the velocity of blood flow in the tumor vessels and presence of central dominant vessels in the tumor [9]. Although color Doppler flow imaging could obtain the information on blood flow in the lesion, under the condition of insufficient blood supply, extremely high intraocular pressure, low blood flow velocity, or because of the limited sensitivity of the instrument for the detection of blood flow, it may only be able to exhibit low blood flow signal (if any) in the lesion, leading to inaccurate diagnosis or even misdiagnosis as nontumorous lesion [10,11].…”
Section: Discussionmentioning
confidence: 99%